Effect of Integrated Weed Management Practices on Weed Growth and Yield of Sorghum in Winter (Bangladesh Agronomy Journal, 2025)
The field experiment was conducted at Agronomy Division, Bangladesh Agricultural Research Institute, Gazipur, during Rabi season of 2022-23 and 2023-2024 to study the effect of integration of chemical and cultural methods for weed management in sorghum. There were seven treatment viz. T1 = Two hand weeding at 25 and 40 days after sowing (DAS), T2 = Atrazine @ 2 L ha−1 spraying as pre-emergence + one hand weeding at 25 days after sowing (DAS), T3 =Atrazine @ 2 L ha−1 spraying as pre-emergence + weeding by BARI weeder at 25 days after sowing (DAS), T4 = Atrazine @ 2 L ha−1 spraying as post-emergence at 25 DAS + one hand weeding at 40 days after sowing (DAS), T5 = Pendimethalin @ 3 L ha−1 spraying as pre-emergence + one hand weeding at 25 days after sowing (DAS), T6 = Pendimethalin @ 3 L ha−1 spraying as pre-emergence and T7= No weeding and no herbicide were included in the experiment. Barnyard grass (Echinochola crusgalli), Harkuch (Enhydra fluctuans), Nutsedge (Cyperus rotundus) and Jersey cudweed (Gnaphalium affine) were the common and dominant weeds in the sorghum field. Results showed that the highest weed control efficiency (WCE) (84.4% at 25 days after establishment (DAE) and 90.2% at 45 DAE at 2022-23 and 85.28% at 25 DAE and 81.58% at 45 DAE at 2023-24) was found in T2 treatment. Significantly the highest two years average yield (3.64 kg ha−1) was obtained from T5 treatment. The highest gross return of (Tk. 109300 ha−1) and benefit cost ratio (BCR) (2.01) were also obtained from T5 treatment. From the result it might be concluded that, two herbicides (Atrazine @ 2 L ha−1 spraying as pre-emergence + one hand weeding at 25 DAS and Pendimethalin@ 3 L ha−1spraying as pre-emergence + one hand weeding at 25 DAS) were found economical by recording higher net returns and BCR compared to control.Bangladesh Agron. J. 2024, 27(2): 78-89